3D survey and semantic analysis for the documentation of built heritage. The case study of Palazzo Centrale of Pavia University - Alessia Miceli; Marco Morandotti; Sandro Parrinello (Vitruvio: International Journal of Architectural Technology and Sustainability)
In the procedures regarding built heritage documentation, the process of representing the object in a digital environment is characterized by a high level of complexity. In fact, the need to process heterogeneous information, referring to quantity, quality and format is one of the main emerging issues. Recent technologies of digitization of our built environment offer excellent performances on data reliability and time of acquisition. On the other hand, they bring about new challenges regarding how to define methodologies and strategies to effectively elaborate such information.